O acesso do surdo ao ensino superior: limites e avanços das políticas educacionais de inclusão - Mesquita, Leila Santos de (2013)
This paper discusses the problem that permeates the education of deaf people with regard to their access to higher education on the progress of the educational policies of inclusion. Amongst our guiding questions we highlight the limits and achievements of educational policies as well as what hinders the continued academical formation of this social group. We point in what manner has occurred access of deaf subjects to higher education within the limitations and advances in educational policies of inclusion. Our research was anchored on a qualitative approach, based on interactive method, analysis of educational policies content and study of subject discourses. The research was made, using a questionnaire as instrument of data collection, with deaf graduates from a state school of Pernambuco with deaf graduates from high school. We devised that despite advances in educational policy of inclusion there are still many barriers for deaf people to gain access to universities. Within those are the appropriation of the Portuguese language by deaf subjects and communication barriers established by the lack of recognition of sign language as a first language for the deaf. We perceived as advancement the linguistics policies, especially the proposed bilingual education for the deaf. However effective operationalization of this proposal is a clear limitation we could devise as well.